Identification of Indonesian Language Learning Strategies of Grade III Students of Public Elementary School - Ajamsaru, Ramses Hiskia; Saputro, Isnaini Eddy; Lestari, Lestari (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The intent of this study was to identify the Indonesian language learning strategies of elementary school students. This research is a qualitative descriptive study employing a content analysis methodology. This research was carried out at Public Elementary School 35 Kimindores. Data was gathered utilizing the Language Learning Strategies (LLS) questionnaire, and the content was examined, including responses and informant narratives. The data analysis employed a qualitative descriptive methodology. The results indicated that the six learning strategies-memory, cognitive, compensatory, metacognitive, affective, and social benefited the third-grade children at Public Elementary School 35 Kimindores. The metacognitive tactics were the most beneficial. Among the six techniques, metacognitive is the most prevalent. Students can promptly focus on errors in their learning while still attending to teachers or classmates during discussions or explanations of each subtheme accurately. Furthermore, students learn to enhance their proficiency in the Indonesian language, devise a study timetable to allocate sufficient time for study, seek peers for collaborative learning, identify numerous opportunities to practice reading Indonesian texts, and evaluate their learning outcomes following each daily practice or semester examination.